The -Fractional Analogue for Gronwall-Type Inequality - Thabet Abdeljawad; Jehad O. Alzabut (Journal of Function Spaces and Applications, 2013)
We utilize -fractional Caputo initial value problems of order to derive a -analogue for Gronwall-type inequality. Some particular cases are derived where -Mittag-Leffler functions and -exponential type functions are used. An example is given to illustrate the validity of the derived inequality.